MALPRAKTIK DAN CONTEMPT OF COURT - Huda, Afiful; Sprinda, Mila Novia (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
The research discusses two different legal phenomena that often influence public trust in the judicial system and certain professions in Indonesia. First, malpractice, which refers to unprofessional conduct by individuals in various professions such as medical, legal, accounting, and others. Second, Contempt of Court, which involves actions considered to insult or undermine the dignity of the court. In the first part, the definition and types of malpractice are outlined, with an emphasis on errors and negligence leading to patient harm or even death. This phenomenon is linked to differences in ethics, codes of conduct, and underlying legal violations. Furthermore, the discussion of Contempt of Court highlights behaviors deemed to insult or harm the credibility of the court. In the Indonesian context, the lack of specific regulations has led to the spread of this offense across various articles in criminal law, making law enforcement and consistent understanding of actions considered as